Analisis Akuntansi Persediaan Berdasarkan PSAP No 05 Tahun 2010 Pada Kantor Perwakilan BKKBN Provinsi Papua Barat - Simanjuntak, Verawati; Parastri, Desirianingsih Haryati; Sudarwadi, Hustianto (Fakultas Ekonomi dan Bisnis Universitas Papua, 2023)
ABSTRACT The Representative Office of the National Population and Family Planning Board (i.e. BKKBN) in West Papua is a government agency dedicated to managing population growth within the West Papua Province. At the BKKBN Representative Office, there are two types of supplies: office stationery for internal use and supplies distributed to the community.The aim of this research is to analyze the accounting standards at The National Population and Family Planning Board Representative Office of West Papua and evaluate their conformity with PSAP No. 05 of 2010 regarding inventory management at the West Papua Province BKKBN Representative Office. This research employs descriptive qualitative methods, utilizing data from the 2010 Financial Report and interviews. The results of this research include the classification of supplies at the West Papua Province BKKBN Representative Office, consisting of stationery and medicine supplies designated for distribution to the community. Inventory recognition at the West Papua Province BKKBN Representative Office occurs upon the arrival of goods at the warehouse. Inventory calculations follow the FIFO method. Expenses related to inventory usage are documented as inventory expenses in the Operational Report. Additionally, disclosures regarding damaged or defective goods are included in the notes to financial reports, and inventory measurement policies are also detailed within these notes. The inventory accounting procedures at the West Papua Province BKKBN Representative Office, including classification, recognition, measurement, inventory expenses, and disclosure, align with PSAP No. 05 regarding Inventory. Keywords: PSAP 05, Inventory Accounting, BKKBN ABSTRAK Kantor Perwakilan BKKBN Provinsi Papua adalah instansi pemerintah yang bergerak dalam bidang pelayanan dalam menanggulangi meedaknya penduduk di Provinsi Papua Barat. Pada Kantor Perwakilan BKKBN terdapat dua jenis persediaan, yaitu Persediaan ATK dan Persediaan yang diserahkan kepada Masyarakat. Tujuan pernelitian ini untuk menganalisis penerapan akuntansi persediaan di Kantor Perwakilan BKKBN Provinsi Papua Barat dan menganalisis kesesuaian penerapan akuntansi persediaan di Kantor Perwakilan BKKBN Provinsi Papua Barat dengan PSAP No. 05 Tahun 2010 tentang Persediaan. Penelitian ini menggunakan metode kualitatif deskriptif. Jenis data menggunakan Laporan Keuangan tahun 2010 dan wawancara. Hasil penelitian ini Klasifikasi persediaan pada Kantor Perwakilan BKKBN Provinsi Papua Barat berupa persediaan ATK dan Persediaan 0bat-obatan yang akan diserahkan ke masyarakat. Pengakuan persediaan pada Kantor Perwakilan BKKBN Provinsi Papua Barat dapat diakui apabila barang sudah sampai di gudang. Perhitungan persediaan menggunakan metode FIFO. Untuk beban persediaan yang sudah digunakan dicatat sebagai beban persediaan pada Laporan Operasional. Sedangkan untuk pengungkapan pada untuk barang yang rusak atau cacat dicantumkan pada CaLK dan untk kebijakan pengukuran persedian dicantumkan pada CaLK. Penerapan akuntansi persediaan pada Kantor Perwakilan BKKBN Provinsi Papua Barat untuk Klasifikasi, Pengakuan, Pengukuran, Beban Persediaan, dan pengungkapan persediaan sudah sesuai dengan PSAP No.05 tentang Persediaan. Kata Kunci: PSAP 05, Akuntansi Persediaan, BKKBN